Enhancement of food safety – antimicrobial effectiveness of cold plasma treatments - Irina SMEU (Annals of the University Dunarea de Jos of Galati. Fascicle VI: Food Technology, 2014)
Cold plasma treatment proved to be a flexible, efficient, chemical-free antimicrobial process and it can represent an easy to use sanitizing method for the food industry that does not require special temperature, humidity or pressure conditions. This paper reviews the classification of plasma and the main cold plasma generating devices used in the recent years to enhance food safety. A research of available literature was also conducted to identify the antimicrobial mode of action of cold plasma treatment as well as advantages and key limitations of this technique when applied to different food products such as fruits, vegetables, meat and milk. The study revealed that further development of this method will have to be carried out, allowing better understanding of the complex interactions during applications and its restrictions, as well as practice outlook.